THU0205 The temporal appearance of symptoms and signs in churg strauss syndrome: From the prodromal phase to damage. (23rd January 2014) - Baldini, C.; Pepe, P.; Latorre, M.; della Rossa, A.; Seccia, V.; Iannicelli, P.; Giorgerini, V.; Galimberti, S.; Tavoni, A.; Paggiaro, P.L.; Bombardieri, S.
Abstract : Objectives: to characterise the clinical presentation of Churg Strauss syndrome (CSS) in a monocentric cohort of patients and to assess the response to treatment and the long-term outcome of the disease. Methods: We reviewed the case records of 48 CSS patients (ACR criteria) who had attended our Units in the decades between 1989 and 2011. Patients' cumulative clinical and immunologic features were collected. The lag time between the diagnosis of CSS and the onset of each CSS clinical and serological manifestation was recorded in order to group the disease features according to their mean periods of appearance. Logistic regression analysis was applied to explore clinical and serological associations. Results: Forty-eight CSS patients (23F:25M) were enrolled in the study. Mean age at the time of diagnosis was 48±15 years; mean follow-up 7.2±5.3 years. The prodromal phase was characterised by asthma and ENT involvement. The diagnosis of asthma preceded the onset of vasculitis by 8.6±11.6 years (range 0-37 yrs). Similarly, ENT involvement preceded systemic manifestations by 6.7±11.2 years. In particular, a diagnosis of rhinosinusitis was made in 44/48 (91.7%) patients whereas sinonasal polyps were detected in 30/48 (62.5%) patients, with the 39% of the patients requiring surgical intervention before CSS diagnosis. General symptoms were documented in >90% of the patients at the diagnosis. Similarly, peripheral nervous system (pns) involvement (19/48; 39.5%), abdominal involvement (15/48, 31%), purpura (16/48, 33%), cardiac involvement (13/48, 27%) and renal involvement (2/48, 4.2%) appeared at the onset of the disease, usually within the first year from the diagnosis. Pulmonary infiltrates (28/48; 58.3%) appeared later with a mean latency from the diagnosis of 2±5 years. Hypereosinophilia was the main biological presenting feature of CSS patients and persisted "grumbling" in the 27% of the cases; mean IgE levels at diagnosis were 641±847 IU/ml vs 155±204 IU/ml at the end of the follow-up. ANCA-MPO, were found in 23/48 (48%) of the patients at the disease onset and in 3/48 (6.3%) at the end of the follow-up. ANCA status correlated with pns involvement (p=0.03), lung infiltrates (p=0.01), cardiac involvement (p=0.03) and with disease relapse over the time (p=0.03). All the patients were treated with corticosteroids alone or in combination with cyclophosphamide or methotrexate. Clinical remission was obtained in 93.75%; relapses occurred in 14 (29%) patients, generally within the first 5 years from the diagnosis and were usually represented by mild disease manifestations (i.e. arthralgias, ENT). Severe disease complications scarcely characterised CSS relapses with the exception of pulmonary infiltrates (9/48). The VDI at the end of the follow up mostly reflected the residual asthma (37/48), the steroids long term side effects (22/48), the ENT damage (29/48) and the sequelae of neural damage which were persistently detectable in 10/19 patients. Conclusions: This study confirmed that damage remains an important problem for patients with CSS despite effective remission-inducing drugs Disclosure of Interest: None Declared